(untitled) (World of finance, 2023)
Introduction. The development of information technologies led to the emergence of new financial instruments, payment systems, methods and payment platforms. Cryptocurrency is a means of circulation and payments fundamentally different from traditional ones. Awareness of the emergence and existence of electronic money is quite high, however, awareness of the mechanism of its functioning and the possibility of using/making calculations, financing projects is low. The puppose of the article is to highlight the main characteristic features of cryptocurrencies, to justify the advantages and disadvantages of cryptocurrencies, to analyze the state, dynamics and development prospects of the cryptocurrency market. Results. Characteristic features of cryptocurrencies include: lack of payment system administration; impossibility of forced return, withdrawal or "freezing" of payments (without access to the owner’s private key). Cryptocurrency is an investment object, and the speculative-investor type of demand for cryptocurrencies is also noted. The authors identified the advantages of using cryptocurrencies, including: equal conditions of use by users, unlimited possibilities of transactions, their transparency, lack of complications in international transfers and the impossibility of blocking or freezing a cryptocurrency wallet and its funds, no commission, open code of cryptocurrency, decentralization. Among the disadvantages of cryptocurrencies are identified: the danger of losing the key to cryptocurrency; the difficulty of returning funds in case of erroneous currency transfer; lack of guarantees for keeping electronic wallets; intervention by hackers; instability of the cryptocurrency exchange rate, dependence of the exchange rate on demand; high energy consumption; distrust of users. The dynamics of the exchange rate of bitcoin and ethereum were analyzed, significant fluctuations in their exchange rate relative to the dollar during the research period were noted. The difference in the views of countries on the issue of regulating the circulation of cryptocurrencies is described (recognition of operations with cryptocurrency as illegal activity, full / partial ban, legalization of legal circulation of electronic money). Conclusions. Barriers and prospects for the development of the electronic money market have been identified. Given the described features of cryptocurrencies, the prospects of recognition / settlement of cryptocurrencies as a financial instrument at the same level as freely convertible currencies (dollar, euro, etc.) are unrealistic and impractical within the framework of the existing mechanisms of functioning of the cryptocurrency market. The prospects for the growth of cryptocurrency circulation in the sectors of NFT-tokens (in games, music, art, sports) were noted.